(untitled) (American Journal of Islam and Society, 2013)
This paper is a provocative play on the famous Muslim Brotherhood slogan al-Islām hūwa al-ḥāl (Islam is the solution). While critics of the Muslim Brothers rightly criticized them for the simplicity of their worldview in thinking that religion was a panacea for all of the problems confronting Muslim societies during the late twentieth century, an argument can be made that religion does profoundly matter in the context of the struggle for democracy in the Arab-Islamic world. In the aftermath of the Arab Spring, democratic transitions in North Africa and the Middle East will be dependent on democratically negotiating the question of religion’s role in politics. Here I provide some reflections on this topic with a focus on Tunisia’s transition to democracy.